INTEGRASI SUPPLY CHAIN DAN DAMPAKNYA TERHADAP PERFORMA PERUSAHAAN (Studi Pada Perusahaan Penyedia Jasa Makanan di Semarang) - Umaryanto, Agus; Hendriyanto, Asepta (STIE Totalwin Semarang, 2010)
Supply chain business network that explained as an organization network that involve supplier relationship upstream) and customer downstream). Effectivity of integration on supply will be the key factor for company to reach continuous improvement that make company became competitive. The difference result in applying integration pattern, could be seen at restaurant sector, dept food and beverage (hotel) and fact food restaurant. The underlined is that each sector are different in integration factor and the influence to company performance. Based on that problem, the research question is : how the integration pattern characteristic of supply chain and implementationÂ ( direction and level) from each sectors. Sample amount of this research is 31 company that include of 15 restaurant, 10 dept food and beverage hotel and 6 fast food restaurant. Based on the result of regression equation knows that integration pattern supply chain management positively affecting dept food and beverage company performance in Semarang. Variation of variabel company performance that can be explained by variation of integration pattern supply chain management is 69% and the rest 31% affecting by another variable outside variable that used in this research. There is a significance difference between restaurant in Semarang that consist of restaurant, food and beverage division and fastfood restaurant with integration pattern supply chain management and company performance.